PENERAPAN TEKNIK SEO (SEARCH ENGINE OPTIMISATION) DENGAN METODE ONPAGE DAN OFFPAGE PADA WEBSITE CARGORIAU.COM - Fauzan Azim (RJOCS (Riau Journal of Computer Science), 2019)
This study aims to determine the application of SEO (Search Engine Optimization) techniques on the cargoriau.com website. This research focuses on the application of marketing by utilizing SEO with onpage and offpage methods in the development and improvement of freight forwarding services, cargo and expeditions in the regency and city areas in Riau Province. The website "www.cargoriau.com" is one of the websites supporting Zataka Express Group's freight forwarders and cargo promotions. Data collection techniques in this study are by interview, observation and documentation. The data analysis techniques used in this study include transcripts of interviews, data reduction, analysis, and interpretation of data. The results of data analysis can then be concluded. The results of SEO (Search Engine Optimization) conducted by researchers on the website "www.cargoriau.com" yielded results in the increasing number of service users, Cargo and Expeditions to various districts and cities in Riau Province. This is because more traffic from website visitors "www.cargoriau.com" and the website is indexed on the first page of Google